The World Health Organization's global target for reducing childhood stunting by 2025: rationale and proposed actions. Issue 3 (18th September 2013) - de Onis, Mercedes; Dewey, Kathryn G.; Borghi, Elaine; Onyango, Adelheid W.; Blössner, Monika; Daelmans, Bernadette; Piwoz, Ellen; Branca, Francesco
Abstract: In 2012, the World Health Organization adopted a resolution on maternal, infant and young child nutrition that included a global target to reduce by 40% the number of stunted under‐five children by 2025. The target was based on analyses of time series data from 148 countries and national success stories in tackling undernutrition. The global target translates to a 3.9% reduction per year and implies decreasing the number of stunted children from 171 million in 2010 to about 100 million in 2025. However, at current rates of progress, there will be 127 million stunted children by 2025, that is, 27 million more than the target or a reduction of only 26%. The translation of the global target into national targets needs to consider nutrition profiles, risk factor trends, demographic changes, experience with developing and implementing nutrition policies, and health system development. This paper presents a methodology to set individual country targets, without precluding the use of others. Any method applied will be influenced by country‐specific population growth rates. A key question is what countries should do to meet the target. Nutrition interventions alone are almost certainly insufficient, hence the importance of ongoing efforts to foster nutrition‐sensitive development and encourage development of evidence‐based, multisectoral plans to address stunting at national scale, combining direct nutrition interventions with strategies concerning health, family planning, water and sanitation, and other factors that affect the risk of stunting. In addition, an accountability framework needs to be developed and surveillance systems strengthened to monitor the achievement of commitments and targets.